Effect of hydraulic and solid ballast on agricultural tractor performance - Zimmermann, Gabriel Ganancini; Savi, Daniel; Auler, André Carlos; Strapasson Neto, Lauro; Jasper, Samir Paulo (Ciência agronômica, 2022)
ABSTRACT The efficiency of the agricultural tractor can be increased with its assertive operational adequacy, ballasting being one of the fundamental factors for obtaining good performance levels, as it is closely related to energy and operational performance. Thus, the objective of this experiment was to evaluate the effect of hydraulic and solid ballast, under different fractions, on the performance of the agricultural tractor. The banded experiment was conducted in a randomized block design, with the treatments consisting of the five configurations of base mass (B0), B0 + 40% hydraulic (HB 40%), B0 + 40% solid (SB 40%), B0 + 75% hydraulic (HB 75%) and B0 + 75% solid (SB 75%), and four target speeds, with five repetitions, totaling 100 experimental units. To determine the efficiency of the tractor, 4 x 2 AFWD with a rated power of 125.2 kW, the parameters of wheel slip, engine rotation, hourly and specific fuel consumption, power, power, and efficiency in the drawbar, operating speed and thermal efficiency of the engine were monitored. The collected data were subjected to analysis of variance/ when significant, submitted to the Tukey test and regression analysis. The obtained results verified that using the hydraulic ballast in the fraction of 75% presented superiority in the energetic and operational performance, highlighting the engine rotation, force in the drawbar, operational speed, and specific fuel consumption. The increase in operational speed can provide gains in energy and operational efficiency; however, it can generate overload on the engine in some ballast configurations.